COVID-19 associated mucormycosis in head and neck region of pediatric patients: a life-threatening disease in current pandemic - Swain, Santosh Kumar (International Journal of Contemporary Pediatrics, 2021)
Mucormycosis is a severe form of fungal infection and often affect immunocompromised patients. It is associated with high morbidity and mortality and characterized by extensive angioinvasion and necrosis of the affected tissue. It is potentially fatal invasive fungal infection in the pediatric age group. It results in rapid spread of the disease with tissue destruction and its nature of angioinvasion can cause wide-spread dissemination. Currently this dreaded mucormycosis is rising among COVID-19 pediatric patients during their treatment period or after their discharge from hospital. It is also called COVID-19 associated mucormycosis (CAM) or black fungus. Classically, uncontrolled diabetes mellitus (DM) and other immunosuppressive conditions or corticosteroid therapy during COVID -19 treatment are known risk factors for causing mucormycosis in pediatric patients. Early identification and prompt treatment in pediatric patients with CAM are required. In the head and neck area, rhino-orbital-cerebral mucormycosis is a fatal clinical entity associated with COVID-19 infections result in higher morbidity and mortality of the pediatric patients. Aggressive endoscopic surgical debridement for local control and appropriate systemic antifungal treatment will help to improve the prognosis and survival of the patients. The aim of this review article is to discuss the detail of epidemiology, etiopathology, clinical profile, diagnosis and current treatment options of the CAM in children.